Bio‐Inspired Preparation of Fibrin‐Boned Bionanocomposites of Biomacromolecules and Nanomaterials for Biosensing. (26th May 2014) - Han, Fangfang; Qi, Xin; Li, Lingyan; Bu, Lijuan; Fu, Yingchun; Xie, Qingji; Guo, Manli; Li, Yanbin; Ying, Yibin; Yao, Shouzhuo
<x xml:space="preserve">Abstract</x> Learning from nature is one of the most promising ways to develop advanced functional materials. Here, inspired by blood coagulation, novel fibrin‐boned bionanocomposites are reported as efficient immobilization matrices of biomacromolecules and nanomaterials for biosensing. Glucose oxidase (GOx), Au nanoparticles (AuNPs), and Fe3O4 magnetic nanoparticles (MNPs) are adopted as the model biomacromolecules and nanomaterials. By integrating the thrombin‐triggered coagulation of fibrin with advanced surficial modification techniques, four kinds of immobilization strategies are developed and evaluated. Digital imaging, UV‐vis spectroscopy, scanning/transmission electron microscopy, electrochemical methods, and N2 adsorption‐desorption isotherms are used to investigate the formation, immobilization efficiency, and performance of various bionanocomposites. The fibrin‐boned networks show inherent biocompatibility, excellent adsorbability, porosity, and functionalization ability, endowing the bionanocomposites with high efficiencies in capturing AuNPs, MNPs and GOx (99%, 98%, and 57% captured under the given conditions, respectively), as well as significant mass‐transfer and biocatalysis efficiencies. Therefore, the fibrin‐boned bionanocomposites show great potential for biosensing, for example, a fibrin‐AuNPs‐GOx‐glutaraldehyde bionanocomposites modified Au electrode is highly sensitive to glucose (145 μA cm−2 mM−1) allowing for a limit of detection down to 25 nM, being much superior to those of the reported analogues. The presented experimental platform/strategy may find wide applications in the development of other bio/nano‐materials/devices.